Using fluid structure interaction technique to investigate the effect of vibration on bileaflet mechanical heart valve deformation - Kadhim, S.K. (Asian Research Publishing Network, 2016)
Fluid-Structure Intraction computer simulation technique is used to study effect of vibration due to blood flow on bileaflet mechanical heart valves structure including the deflection connection in the pin of the valve. This technique is used is to predict the deformation of the bileaflet mechanical heart valve structure, which occurs due to the heart beats. Five heartbeat models were used in this study which is 80, 90, 100, 110, and 120 BPM at variable leaflet angles of 25o, 63o and 85o. To determine the deformation, the equivalent (von-Mises) stress at the connection pin of a bileaflet mechanical heart valve were calculated and compared with the equivalent (von-Mises) stress of the connection pin in the literature. It was found when the heartbeat increased from 80 BPM to 120 BPM, 62 increase in von-Mises stress values were recorded at the valve connection pin at a fully closed angle of 25Â°. The increase in heartbeat periodically for the lifetime may weaken the valve's connecting pin and housing, which may cause damage to the bileaflet mechanical heart valve components. Â©2006-2016 Asian Research Publishing Network (ARPN).